JMBE Supports 20 Years of Teaching Excellence at ASMCUE and Offers ASM Laboratory Safety Guidelines - Christopher J. Woolverton (American Society for Microbiology, 2013)
Since 2010, JMBE has included the abstracts from the ASM Conference for Undergraduate Educators (ASMCUE), providing authors a citation for their work in biology education. This year ASM celebrates the 20th anniversary of the ASMCUE, so congratulations to the abstract authors published in this issue for being a part of this significant milestone. Also of note is the Biosafety Guidelines for Teaching Laboratories, authored by Elizabeth A. B. Emmert and the ASM Task Committee on Laboratory Biosafety. Two enhancements to ensure the long-term sustainability of the journal were introduced with this issue: easy to follow training videos that complement the printed guidelines for authors and reviewers, and opportunities for print and online advertising.